64 Effects of grazing cool-season cover crops on forage and animal performance. (28th November 2020) - Carrell, Russell C; Dillard, Sandra L; Mullenix, Mary K; Gamble, Audrey; Muntifering, Russ B
Abstract: Utilization of cool-season cover crops has been shown to increase soil health and cash crop performance in minimum tillage cash crop systems. Though evidence that grazing of cover crops can be viable is limited. Our objective was to determine animal and forage performance when grazing a cool-season annual cover-crop. Twelve 1.2 ha pastures were established in a forage mix consisting of black oats (Avena strigose), cereal rye (Secale cereal), crimson clover (Trifolium incarnatum), and T-raptor (Brassica napus × B. rapa) and randomly allocated to be grazed either 0, 30, 60, or 90 days. Three tester steers were randomly placed in each paddock with the exception of control paddocks and allowed ad libitum grazing. Animals were weighed every 30 d for determination ADG and total gain (TG). Forage was harvested bi-weekly and analyzed for NDF and ADF using an ANKOM fiber analyzer (ANKOM Tech, Macedon, NY). All data were analyzed using MIXED procedure of SAS version 9.4 (SAS Inst., Cary, NC). Differences were found in ADG between 90 and 60 days grazed (4.2 ± 0.12 vs. 2.8 ± 0.12 kg/d; P < 0.01) and 90 and 30 days grazed (4.2 ± 0.12 vs 2.7 ± 0.12 kg/d; P < 0.01). Differences in TG were detected between 90 and 60 days grazed (819 ± 13.35 vs. 386.67 ± 13.35 kg; P < 0.01), between 90 and 30 days grazed (819 ± 13.35 vs 261.33 ± 13.35 kg; P < 0.01), and between 60 and 30 days grazed (386.67 ± 13.35 vs 261.33 ± 13.35 kg, P < 0.01). No differences in NDF (44.86%, P = 0.99) or ADF (27.20%, P = 0.92) were detected between treatments. These results indicate that different grazing periods could influence cattle growth and performance without negatively impacting forage quality and production.